NiFe-CN catalysts derived from the solid-phase exfoliation of NiFe-layered double hydroxide for CO2 electroreduction. (3rd August 2022) - Fu, Yingke; Chen, Lin; Xiong, Ying; Chen, Hao; Xie, Ruishi; Wang, Bing; Zhang, Yaping; Liu, Tianxia; Zhang, Ping
Abstract : The strategy of preparing a CO2 RR catalyst on the basis of solid-phase exfoliation helps to fully expose the catalytic centers of Ni and Fe, and provides a channel for proton transfer, so that the catalyst exhibits excellent performance. Abstract : The development of efficient carbon dioxide reduction reaction (CO2 RR) catalysts is one of the practical solutions to the current environmental problems. Usually, metal-doped catalysts are used for the CO2 RR, but the metal elements can easily aggregate, resulting in a reduction in the catalytic performance. In this study, NiFe-LDH was exfoliated to single layer by a solid-phase exfoliation strategy, wherein Ni and Fe were doped on the char material owing to the pyrolysis of the solid-phase exfoliation agent, and the NiFe-CN catalyst with a gauzy and porous structure was obtained. The catalyst possessed excellent catalytic performance; particularly, when the mass fraction of NiFe-LDH was 1 wt%, the prepared catalyst (NiFe-CN-1) showed a faradaic efficiency of 93.5% for the reduction of CO2 to CO at −0.8 V ( vs. reversible hydrogen electrode (RHE)) with a CO current density of 10.4 mA cm −2, which was due to the sufficient exposure of active sites and efficient proton transfer channels of NiFe-CN. This strategy provides a new idea to easily mass produce CO2 RR electrocatalysts in an environmentally benign way.